2012
DOI: 10.1038/onc.2012.165
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced expression of CK2 kinase subunits is sufficient to drive epithelial-to-mesenchymal transition by Snail1 induction

Abstract: Epithelial-to-mesenchymal transition (EMT) is closely linked to conversion of early-stage tumours into invasive malignancies. Many signalling pathways are involved in EMT, but the key regulatory kinases in this important process have not been clearly identified. Protein kinase CK2 is a multi-subunit protein kinase, which, when overexpressed, has been linked to disease progression and poor prognosis in various cancers. Specifically, overexpression of CK2α in human breast cancers is correlated with metastatic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 51 publications
10
81
0
Order By: Relevance
“…Color images available online at www.liebertpub.com/scd expression in corneal stem cells [41,42] and circulating keratinocyte progenitor cells [32]. Moreover, the EpSCs in the present study were positive for Casein Kinase 2b, which is reputed to inhibit the development of the mesenchymal morphology and phenotype [37,45], and plays an important role in the functional regulation of epithelial cells [46][47][48].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Color images available online at www.liebertpub.com/scd expression in corneal stem cells [41,42] and circulating keratinocyte progenitor cells [32]. Moreover, the EpSCs in the present study were positive for Casein Kinase 2b, which is reputed to inhibit the development of the mesenchymal morphology and phenotype [37,45], and plays an important role in the functional regulation of epithelial cells [46][47][48].…”
Section: Discussionmentioning
confidence: 82%
“…S5B, C), but were clearly positive for the proliferation marker Ki67 [36] (Supplementary Fig. S6) and the epithelial marker Casein Kinase 2b [37] (Supplementary Fig. S6), both of which sharply decreased on differentiation (Supplementary Fig.…”
Section: Epidermis-derived Cells Are Classified As Epscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their expression and extent of post-translational modification, the activity of protein kinases can be modulated by allosteric mechanisms regulated by protein-protein interactions. For example, the activity of CK2 is modulated by the ratio of catalytic (alpha) to regulatory (beta) subunits as the latter binds and inactivates the catalytic activity of CK2 alpha (36,38). We found that this ratio of CK2 catalytic to regulatory subunit was modulated by in vivo growth conditions (Fig.…”
Section: Pi3k Inhibitors Modulate Markers Of Apoptosis Differently Inmentioning
confidence: 73%
“…4A). This is an interesting observation, as it is known that CK2 activity is regulated by the ratio between the alpha and beta subunits (35)(36)(37) in addition to its absolute expression (38,39). CK2 beta binds to CK2 alpha, resulting in the formation of an inactive polymeric complex; thus, an alteration in CK2 subunit ratios (Fig.…”
Section: Differential Regulation Of Kinase Expression and Phosphorylamentioning
confidence: 99%